Explosive attack: Lessons learned in Seyed Al Shohada mosque attack, April 2008, Shiraz, Iran - Shahram Paydar; Maryam Sharifian; Shahram Boland Parvaz; Hamid Reza Abbasi; Mohamad javad Moradian; Jamshid Roozbeh; Saman Nikghbalian; Mohammad Mahdi Sagheb; Fariborz Ghaffarpasand; Oveis Salehi; Javad Dehghani (Journal of Emergencies, Trauma and Shock, 2012)
Introduction: The threat of explosive attacks has become a worldwide problem. Bombing is the preferred method of attacks. These attacks result in specific physical and psychiatric trauma. In this paper, we present an epidemiologic description of the physical injuries of patients who survived the explosive attack in Seyed Al Shohada mosque April 2008 Shiraz, Iran. Materials and Methods: All medical records of the patients admitted at Shiraz Hospitals on April 2008 due to Seyed Al Shohada mosque bombing attacks, Shiraz, Iran, were reviewed. Results: A total of 202 patients were referred to the hospitals over 24 h following the terrorist attack. One hundred sixty-four patients were admitted for short periods of observation (<24 h). Thirty-eight patients needed more than 1 day of hospitalization. The mean age of the patients was 26.2 (range 2 to 51) years. One hundred thirty-five (66.8%) patients were males. Twenty-six (12.8%) were children. Burn was the most prevalent cause of admission. Five (13.5%) patients needed chest tube insertion and eight (21%) needed skin grafts due to burn. Overall, 12 patients expired (5%). Three (25%) of them were children (2 and 6, and 11 years old). Mortality rate was significantly higher among the children than adults (P value <0.05). The most important cause of death was head trauma which was seen in five (41.6%) of the expired patients followed by burn (including air way burn) in four (33%), and internal bleeding in three (25%). Patients with head trauma had significantly a higher rate of mortality than other patients (P value <0.05). Discussion: Following a bombing attack, numerous victims were brought to the emergency unit suffering from a combination of multi-organ injuries caused by the blast, penetrating injuries caused by shrapnel and other debris, and burns. It is important for a physician to be familiar with the clinical features and treatments of explosive attacks victims. Early management of patients at the scene and hospital may save their life.